2010
DOI: 10.1073/pnas.1012568107
|View full text |Cite|
|
Sign up to set email alerts
|

Soluble amyloid precursor protein (APP) regulates transthyretin and Klotho gene expression without rescuing the essential function of APP

Abstract: Amyloidogenic processing of the amyloid precursor protein (APP) generates a large secreted ectodomain fragment (APPsβ), β-amyloid (Aβ) peptides, and an APP intracellular domain (AICD). Whereas Aβ is viewed as critical for Alzheimer's disease pathogenesis, the role of other APP processing products remains enigmatic. Of interest, the AICD has been implicated in transcriptional regulation, and N-terminal cleavage of APPsβ has been suggested to produce an active fragment that may mediate axonal pruning and neurona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
116
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(123 citation statements)
references
References 50 publications
5
116
1
1
Order By: Relevance
“…Surprisingly, both phenotypes were found to be rescued by either a C-terminal truncation of apl-1 or the soluble N-terminus, showing that the highly conserved C-terminus is not required for apl-1 function in the worm [15,16]. This differs from the mammalian system in which the APP C-terminus is essential for viability on a nonredundant background (see discussion under 'KI models [18,19]. Hornsten et al [15] were unable to accomplish rescue using the Cterminus alone, indicating, together with the other rescue experiments, that the N-terminus is the primary functional domain of APL-1 in the worm.…”
Section: Elegansmentioning
confidence: 98%
See 2 more Smart Citations
“…Surprisingly, both phenotypes were found to be rescued by either a C-terminal truncation of apl-1 or the soluble N-terminus, showing that the highly conserved C-terminus is not required for apl-1 function in the worm [15,16]. This differs from the mammalian system in which the APP C-terminus is essential for viability on a nonredundant background (see discussion under 'KI models [18,19]. Hornsten et al [15] were unable to accomplish rescue using the Cterminus alone, indicating, together with the other rescue experiments, that the N-terminus is the primary functional domain of APL-1 in the worm.…”
Section: Elegansmentioning
confidence: 98%
“…For APP, there are two knockout (KO) alleles [28,29], one hypomorphic allele [30], two conditional alleles [31,32], four defined truncation KI alleles [18,19,33] and two C-terminal point mutation KI alleles reported [34,35].…”
Section: App Models In Micementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, these include soluble Amyloid precursor protein, which upregulates α-Klotho expression (Li et al, 2010), indicating that in pathological amyloidogenic conditions such as Alzheimer's Disease, proper α-Klotho expression might be impaired. Consistently, α-Klotho is decreased in the serum and brain of AD animal models (Kuang et al, 2014;Massó et al, 2015) and also in the CSF of humans (Semba et al, 2014).…”
Section: Could Increasing α-Klotho Treat Neurodegenerative Disease?mentioning
confidence: 99%
“…In addition, there is evidence that soluble APP fragments (sAPP) of the ectodomain can modulate gene transcription in stimulating downstream signaling through unknown sAPP receptor(s) (14). Accumulation of intracellular A␤ species in neuronal cells before plaque formation leading to concomitant loss of MAP2 expression suggested that A␤ may affect expression or turnover of other proteins (15)(16)(17).…”
Section: Recently the Impact Of App Metabolites (App Intracellular Fmentioning
confidence: 99%